2018
DOI: 10.15252/embr.201846512
|View full text |Cite
|
Sign up to set email alerts
|

Co‐inhibition of immunoproteasome subunits LMP2 and LMP7 is required to block autoimmunity

Abstract: Cells of hematopoietic origin express high levels of the immunoproteasome, a cytokine‐inducible proteasome variant comprising the proteolytic subunits LMP2 (β1i), MECL‐1 (β2i), and LMP7 (β5i). Targeting the immunoproteasome in pre‐clinical models of autoimmune diseases with the epoxyketone inhibitor ONX 0914 has proven to be effective. ONX 0914 was previously described as a selective LMP7 inhibitor. Here, we show that PRN1126, developed as an exclusively LMP7‐specific inhibitor, has limited effects on IL‐6 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 44 publications
6
74
1
1
Order By: Relevance
“…Two new findings have changed our knowledge in this respect. First, recent evidence unraveled that pre-clinically efficacious doses of ONX 0914 inhibit both, LMP7 and LMP2 ( 64 ), which explains the LMP2-co-dependency of ONX 0914-treatment effects in T cell activation (Figure 1 ). Second, while IP expression in lymphoid cells is known for decades, the high extent to which IPs account for the total proteasome content of naïve lymphocytes was underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Two new findings have changed our knowledge in this respect. First, recent evidence unraveled that pre-clinically efficacious doses of ONX 0914 inhibit both, LMP7 and LMP2 ( 64 ), which explains the LMP2-co-dependency of ONX 0914-treatment effects in T cell activation (Figure 1 ). Second, while IP expression in lymphoid cells is known for decades, the high extent to which IPs account for the total proteasome content of naïve lymphocytes was underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the tumor-suppressive potential of ONX 0914 ( 60 , 61 ), pre-clinical research utilizing this compound and other i-proteasome-selective inhibitors revealed additional putative clinical scenarios, where such drugs might improve current medical treatment. Pioneering work by the Groettrup group and others highlighted the therapeutic potential of i-proteasome inhibitors for mitigation of autoimmune-driven inflammatory tissue damage ( 50 , 59 , 62 64 ). KZR-616—an ortholog of ONX 0914 with high selectivity for the human i-proteasome—passed successfully phase I trials and is now in phase II trials for patients with systemic lupus erythematosus.…”
Section: The Proteasome: a Druggable Multi-catalytic Proteasementioning
confidence: 99%
“…Undisputedly, the i-proteasome strongly enhances CD8 + T cell responses for some pathogens [15][16][17], yet there are also examples where the standard proteasome can efficiently compensate for the lack of intact i-proteasome activity [18,19]. Of the different compounds which can experimentally accomplish inhibition of the i-proteasome, ONX 0914 is the best characterized [20,21]. Whereas physiologically desired effects achieved by treatment with the epoxyketone ONX 0914 requires a combined inhibition of both LMP7 and LMP2 [20,21], there is also a LMP7-selective dipeptide inhibitor available which shows potent immunosuppressive activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Of the different compounds which can experimentally accomplish inhibition of the i-proteasome, ONX 0914 is the best characterized [20,21]. Whereas physiologically desired effects achieved by treatment with the epoxyketone ONX 0914 requires a combined inhibition of both LMP7 and LMP2 [20,21], there is also a LMP7-selective dipeptide inhibitor available which shows potent immunosuppressive activity [22]. Another compound referred to as PRN1126, developed as an exclusively LMP7-specific inhibitor shows, however, limited in vivo effects on adverse immune responses [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation